Pengaruh Pola Komunikasi Intrapersonal terhadap Efektivitas Negosiasi dalam Lingkungan Bisnis - Ardy Akbar Pratama; Amanda Putri; Anisa Shelomitha Br Berutu; Jordi Fahrezi; Nabila Assuhaila; Nazwa Pasya; Surya Alfi Rozi Siregar (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study explores the influence of intrapersonal communication patterns on negotiation effectiveness in business environments. Intrapersonal communication, such as self-talk and self-reflection, plays a vital role in emotional regulation and strategic decision-making during negotiations. Using a literature review method, this research analyzes relevant studies to construct a solid theoretical foundation. The findings indicate that managing internal communication enhances confidence, composure, and decision-making accuracy in business negotiations.